High Mobility Materials on Insulator for Advanced Technology Nodes. (31st March 2015) - Schwarzenbach, Walter; Figuet, Christophe; Delprat, Daniel; Veytizou, Christelle; Huyet, Isabelle; Tempesta, Catherine; Ecarnot, Ludovic; Widiez, Julie; Loup, Virginie; Hartmann, Jean-Michel; Besson, Pascal; Deguet, Chrystel; et al.
Abstract : sSOI & SiGeOI substrates have already demonstrated their potential to support digital advanced technology performance roadmap, and are consequently considered in Soitec product roadmap for 10nm technology nodes and beyond. Smart-Cut® process has already demonstrated its benefit to transfer high quality strain silicon and/or SiGe layer from a donor. This paper will show for the first time the results achieved on a 300mm SiGeOI material with high germanium content. Beyond current crystal quality & active layer uniformity, next development will focus on dislocation and surface defect densities improvement.